2021
DOI: 10.1016/j.idm.2021.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical modelling of the spread of COVID-19 on a university campus

Abstract: In this paper we present a deterministic transmission dynamic compartmental model for the spread of the novel coronavirus on a college campus for the purpose of analyzing strategies to mitigate an outbreak. The goal of this project is to determine and compare the utility of certain containment strategies including gateway testing, surveillance testing, and contact tracing as well as individual level control measures such as mask wearing and social distancing. We modify a standard SEIR-type model to reflect wha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 20 publications
2
19
0
Order By: Relevance
“…Finally, like numerous other modeling studies (e.g., (39,41)), we found that surveillance testing with complete sampling can substantially decrease infection rates. Complete sampling requires a vast amount of financial, logistical, and human resources to implement, though, and cannot be launched in Disease X situations until reliable tests are developed.…”
Section: Implication For Future Emerging Infectious Diseasessupporting
confidence: 87%
See 1 more Smart Citation
“…Finally, like numerous other modeling studies (e.g., (39,41)), we found that surveillance testing with complete sampling can substantially decrease infection rates. Complete sampling requires a vast amount of financial, logistical, and human resources to implement, though, and cannot be launched in Disease X situations until reliable tests are developed.…”
Section: Implication For Future Emerging Infectious Diseasessupporting
confidence: 87%
“…Contact tracing was also effective in controlling the transmission rate in simulated results. This intervention has a long and proven track record in public health policy, translates well to novel diseases, and was found to have a comparable effectiveness to surveillance testing with complete sampling in other modeling studies of COVID-19 (41). However, contact tracing requires trained personnel that may not be available at every university.…”
Section: Implication For Future Emerging Infectious Diseasesmentioning
confidence: 99%
“…A set of studies have been conducted to see how the transmission is carried out and to determine the right measures for prevention and distancing. They regard the dependency between pedestrian dynamics and epidemiology [33], the aerosol transmission [34], the mathematical modeling of disease spreading [35], and the risks of students' exposure to COVID-19 in a university building [36] or in other urban settlements [37].…”
Section: Avoiding Crowdsmentioning
confidence: 99%
“…Universities faced many challenges with the decision to offer face-to-face education during the COVID-19 pandemic. When the studies on the creation of a safe campus in the literature are examined, it is seen that studies have focused on effective measures to make face-to-face education safer during the COVID-19 pandemic (Cardonha et al 2022 ; Greenhalgh et al 2021 ; Muller and Muller 2021 ; Gillespie et al 2021 ). Wilson et al ( 2020 ), while studying the reliability of the measures taken at university A in North Carolina and the reasons for the increase in cases, Rafiq et al ( 2021 ), on the other hand, conducted a study to determine the service models, strategies, and role of university libraries during the COVID-19 epidemic.…”
Section: Literature Reviewmentioning
confidence: 99%